Conspecific Presence Improves Episodic-Like Memory in Rats - de França Malheiros, Maria Augustta Sobral; Castelo-Branco, Rochele; de Medeiros, Paulo Henrique Santos; de Lima Marinho, Pedro Emmílio; da Silva Rodrigues Meurer, Ywlliane; Barbosa, Flávio Freitas (Frontiers in Behavioral Neuroscience, 2021)
A number of studies have provided evidence that animals, including rats, remember past episodes. However, few experiments have addressed episodic-like memory from a social perspective. In the present study, we evaluated Wistar rats in the WWWhen/ELM task as single setups and in dyads, applying a long retention interval. We also investigated behaviours that could subserve the emergence of this type of memory. We found that only rats tested in the social setting were able to recollect an integrated episodic-like memory that lasted 24 hours. Additionally, rats in dyads presented higher levels of exploration during the task. When exposed to the testing environment, the dyads exhibited affiliative behaviour towards each other and presented fewer anxiety-like responses. Our findings indicate that the presence of a conspecific could act as a facilitating factor in memory evaluations based on spontaneous exploration of objects and provide empirical support for applying more naturalistic settings in investigations of episodic-like memory in rats.